2018
DOI: 10.1002/cche.10104
|View full text |Cite
|
Sign up to set email alerts
|

Grain constituents and starch characteristics influencing in vitro enzymatic starch hydrolysis in Hungarian triticale genotypes developed for food consumption

Abstract: Background and objectives: Triticale is mostly used for feed but there is an increasing interest for food consumption. In cereals, major storage carbohydrate is starch, whose concentration and composition influence the end use of the grain.Therefore, grain constituents focused on starch characteristics were analyzed in 11 triticale genotypes and compared to wheat and rye. Findings: Significant genotypic variation was detected among the analyzed parameters, in triticale. Starch concentrations (59.2%-66.1%) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The starch degradation was followed by a considerable in-crease in the sugar content from 0.12 ± 0.04 g/100 g at the beginning of the reaction to 7.87 ± 0.88 g/100 g after 60 min. Several factors affect the degree of hydrolysis and amount of sugar produced, including starch type, amylase concentration, granule size, temperature, pH, and substrate/enzyme ratio [21,35,36]. A study by Abebe et al [37] observed a significant increase in the rapidly available glucose content and decrease in starch fractions in teff flour, which is directly related to flour size.…”
Section: Composition Of the Hydrolysatementioning
confidence: 99%
“…The starch degradation was followed by a considerable in-crease in the sugar content from 0.12 ± 0.04 g/100 g at the beginning of the reaction to 7.87 ± 0.88 g/100 g after 60 min. Several factors affect the degree of hydrolysis and amount of sugar produced, including starch type, amylase concentration, granule size, temperature, pH, and substrate/enzyme ratio [21,35,36]. A study by Abebe et al [37] observed a significant increase in the rapidly available glucose content and decrease in starch fractions in teff flour, which is directly related to flour size.…”
Section: Composition Of the Hydrolysatementioning
confidence: 99%
“…11 genotypes of triticale are analyzed and compared with wheat and rye in [13]. The beneficial properties of triticale starch suggest that targeted selection can be used to improve the quality of triticale grains and opens up the possibility of using triticale.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Zhu (2018) summarized triticale's recent uses and nutritional reports, and Langó et al. (2018) concluded that there is an opportunity to develop added‐value products for human consumption from triticale. The main use of wheat is bread making; consequently, wheat flour is highly demanded, so available blends of hard/soft kinds of wheat are constantly searched in order to obtain the desired texture.…”
Section: Introductionmentioning
confidence: 99%